Screening of endophytic fungi for biofuel feedstock production using palm oil mill effluent as a carbon source - Sia, Edwin Sien Aun; Yeo, Joanne Suan Hui; Wong, Julie Wei Ming; Choo, Jenny Cheng Yi.; Changi, Wong; Aazani, Mujahid; Moritz, Müller (Malaysian Society for Microbiology, 2017)
Edwin Sia Sien Aun1, Joanne Yeo Suan Hui1, Julie Wong Wei Ming1, Jenny Choo Cheng Yi1, Changi Wong1, Aazani Mujahid2, Moritz Müller1*